"It Feels Like a Lot of Extra Work": Resident Attitudes About Quality Improvement and Implications for an Effective Learning Health Care System. (July 2017) - Butler, Jorie M.; Anderson, Katherine A.; Supiano, Mark A.; Weir, Charlene R.
Abstract : Purpose: The learning health care system promotes development and application of evidence generated within the health care system to enhance the quality of patient care. The purpose of this study was to understand resident attitudes about quality improvement (QI) in Accreditation Council for Graduate Medical Education–approved programs. Method: Four focus groups were conducted with 45 residents at the University of Utah School of Medicine during September and October 2014. Residents discussed the perceived value of QI and their experiences with QI. Qualitative analysis was conducted iteratively, resulting in a set of constructs that were then consolidated into overarching themes. Results: Five themes emerged from the qualitative analysis. Four of these represented QI participation barriers: challenges with understanding the vision of QI, confusion about basic aspects of QI, a sense that resident contributions to QI are not valued/valuable to the QI process, and challenges with prioritizing responsibilities relating to QI compared with other responsibilities. One theme represented a facilitator of successful QI: factors that make QI work successfully (e.g., clear goals and a sense of being on the "same page"). Conclusions: If resident attitudes about QI do not improve, the culture of the learning health care system is threatened. An important step in enhancing the perceived value of QI is resolving the perceived tension between providing excellent patient care and satisfying other goals. Involving residents more effectively in QI may result in improved attitudes and promote development of a better-functioning learning health care system. Abstract : Supplemental Digital Content is available in the text.